Optimalisasi Digital Akses Beasiswa Pendidikan Bagi Santri Kelas Akhir MA Madrasatul Qur’an Tebuireng Jombang - Surur, Shobihus; Kumala, Akhsinatul; Anshori, Sholihul; Ridlwan, Burhanuddin; Said, Ali; Mughiroh, Ainun Fitri; Mufarrihah, Iftitaahul (Jurnal Pengabdian Masyarakat, 2025)
The rapid advancement of digital technology has created new opportunities in education, particularly in accessing scholarships which are now predominantly online-based. Nevertheless, limited digital literacy remains a critical challenge among students in Islamic boarding schools (santri). This community service program aims to optimize the digital literacy of final-year students at MA Madrasatul Qur’an Tebuireng Jombang in accessing various scholarship opportunities. The study applied a Participatory Action Research (PAR) approach, actively involving students and teachers in every stage of the program. Activities included needs assessment, digital skills training, structured mentoring, evaluation, and collective reflection. Findings revealed significant improvements in students’ basic digital competencies, particularly in email usage, online scholarship registration, and digital document preparation. Based on pre-test and post-test results, average skills improved by 47%. Beyond technical capacity, students developed greater self-confidence in exploring higher education opportunities and building networks with scholarship providers. Teachers, meanwhile, transformed their roles into digital literacy facilitators, reinforcing collaborative learning culture within the pesantren. This program not only benefited individuals but also established a replicable model of best practices for other Islamic boarding schools. Therefore, optimizing digital literacy through participatory approaches proves to be an effective strategy to bridge the digital divide and promote equitable access to education. The sustainability of the program is expected to be ensured through the establishment of a digital scholarship information center, the development of digital literacy volunteers, and the expansion of institutional partnerships.